Effect of Fermented Feed on Growth Performance and Gut Health of Broilers: A Review - Jim Kioko Katu; Tamás Tóth; Balázs Ásványi; Zoltán Hatvan; László Varga (Animals, 2025)
The fermented feed used in broiler production has gained significant attention for its potential to improve growth performance, enhance gut health, and modulate gut microbiota. This review synthesized findings on the effects of both solid and liquid fermented feed in broilers. Fermentation processes enhance nutrient bioavailability; reduce anti-nutritional factors; and generate beneficial metabolites, such as short-chain fatty acids, which contribute to gut health. Incorporating fermented feed in broiler diets has been shown to improve weight gain, the feed conversion ratio, and nutrient absorption by promoting favorable gut morphology changes, including an increased villus height and villus height-to-crypt depth ratios. Additionally, fermented feed fosters a beneficial microbial environment by increasing lactic acid bacteria populations while reducing pathogenic microbes. Fermentation also modulates gut immunity by regulating cytokine production and stimulating immune cell activity. However, challenges such as inconsistent effects on feed intake and growth during the early production stages underscore the need for optimizing fermentation protocols tailored to broiler production systems. Although the implementation of liquid fermented feed presents logistical challenges, research suggests it can significantly improve feed digestibility. Advances in precision fermentation techniques and multi-strain inoculant use hold promise for further improving fermented feed efficacy. Future research should focus on assessing the long-term impacts, economic viability, and environmental sustainability of fermented feed in commercial poultry systems. Overall, fermented feed offers a promising strategy to enhance productivity and sustainability in broiler farming while reducing the reliance on conventional feed additives. This review reflects the body of knowledge at the time of writing.